Teaching Challenges: TIMSS 2015 as a Source of Information about Primary School Teachers' Attitudes towards Their Work - Snežana I. Mirkov; Nataša Z. Lalić-Vučetić (University of Belgrade, Teacher Education Faculty, 2018)
Our intention in this paper was to explore the most striking aspects of teachers' attitudes towards their work and to determine their correlation with the specific elements of teaching organisation and teaching process. We analysed the data obtained from teachers' responses (N = 192) to the questionnaire which was a part of the TIMSS 2015 research. Our goal was to explore how primary school teachers perceive different aspects of teaching process, their satisfaction with their job, and their evaluation of their own level of self-confidence. The questionnaire consisted of questions related to teachers' job satisfaction, their perception of the problems in the teaching process, forms of cooperation among teachers, their self-confidence, and the application of different methods and forms of classroom work in teaching mathematics and science. The obtained data indicate a high level of job satisfaction among primary school teachers. On the other hand, administrative duties and a lack of time to help some students were perceived by the majority of teachers as problems in the teaching process. The application of methods and forms of classroom work is closely related to teachers' level of self-confidence in teaching mathematics and science, as well as to forms of cooperation among teachers. The paper offers suggestions for the improvement of the teaching process.